Exfoliation of graphite into graphene in aqueous solution: an application as graphene/TiO2 nanocomposite to improve visible light photocatalytic activity. Issue 95 (28th September 2016) - Giovannetti, R.; Rommozzi, E.; Zannotti, M.; D'Amato, C. A.; Ferraro, S.; Cespi, M.; Bonacucina, G.; Minicucci, M.; Di Cicco, A.
Abstract : Graphene dispersion (GR) was prepared by liquid-phase sonication of graphite and evaluated by XRD, DLS and UV-Vis analysis. It was used to prepare PP@mgGR–TiO2, showing positive effects on ARS photodegradation under visible light irradiation. Abstract : The aim of this study was the preparation of a graphene/TiO2 heterogeneous catalyst supported on polypropylene for visible light photocatalysis. Aqueous graphene dispersions were prepared by liquid-phase exfoliation of graphite in the presence of a non-ionic surfactant, Triton X-100. The obtained graphene dispersion was characterized by X-ray diffraction, dynamic light scattering and UV-Visible spectroscopy and was subsequently used for the preparation of graphene/TiO2 photocatalyst. As-prepared photocatalysts were tested for the photocatalytic degradation of a refractory dye, Alizarin Red S, in water solutions as target pollutant. Graphene/TiO2 nanocomposites showed higher adsorption of Alizarin Red S on the catalyst surface and higher photocatalytic activity for its degradation under visible light irradiation, in respect to those obtained with pure TiO2 .